ANALYSIS OF FIGURATIVE LANGUAGE IN STEPHEN SANCHEZ’S SONG LYRICS - Wilhelmus Grensideng; I Gusti Ayu Mahatma Agung (FKIP, Universitas Banten Jaya, 2023)
Figurative language is communication with connotation; it may be in the form of a phrase. This research aims to identify the different kinds of figurative language used in the lyrics of Stephen Sanchez’s songs. The theory from Leech (1981) was used to assess the meaning of figurative language, and the theory from Perrine & Arp (1991) was utilized to distinguish the different varieties of figurative language. The findings of this study demonstrated the use of seven figurative languages, including 12.5% of personification, 12.5% of simile, 12.5% of symbol, 25% of metaphor, and 37.5% of hyperbole in Stephen Sanchez’s songs. According to the analysis, hyperbolic figurative language is the most prevalent in Stephen Sanchez’s song lyrics.